Deception Choice and Audit Design - The Importance of Being Earnest - Tim Lohse; Kai A. Konrad; Salmai Qari (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study deception choices and deception detection in a tax compliance experiment. We find large systematic differences in individual deception abilities. Tax payers are conscious about their own deception abilities. The empirical outcomes are in line with a theory suggesting that tax payers make their choices whether to underreport or report truthfully on the basis of their own deception ability. Tax payers with high deception ability are more likely to underreport. This selection effect is stronger if the fines for underreporting are higher. These results provide an (additional) reason why random audits are superior to audits based on discretionary choice.
Keywords: H31; K42; C91; 330